Secret Of The Andes - Clark, Ann Nolan; Charlot, Jean (New York Puffin Books, 1980)
An indian boy who tends ilamas in a hidden valley in peru learns the traditions and secrets of his inca ancestors
American Corner
Winner A Newbery Award Book
11 13
Keywords: English Fiction; English Stories